WEBSITE DESIGNING AT PT WAIRAU INDOSTONE USING MACROMEDI DREAMWEAVER MX 2004 - Donny Fransye Boyoh; Ristyawati Ristyawati, SKom, MMSI (Jurnal Sistem Informasi, 2005)
PT Wairau Indostone is a company engaged in the paving blocks / stone ornamentalsales activities, thus there is need for great efforts in providing optimal informationfor potential customers. As the key to success of this company and service ispromotion detailed information to be able to show an expected level of service. Thepurpose of scientific writing is to provide information sedetil-details to potentialcustomers. In connection with this writing, the framework put forward a theory ofwriting about , is Website design and promotion of the mean of this research is howcompanies promote merchandise using the media of information on the InternetWebsite. From the results of the research note that the company should pay moreattention to the needs of providing information quickly and fully to distributorslocated in areas more distant to increase productivity better.